FIREARMS TRAINING AS A PART OF THE PROFESSIONAL TRAINING OF THE UKRAINIAN BORDER GUARD AGENCY PERSONNEL - Сергій Заболотний; Олег Резнік (Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine, 2022)
The article reveals the features of the firearms training of future officers at the higher military education institutions of the State Border Guard Service of Ukraine. It has been established that the firearms training is an essential part of the professional training of the SBGSU personnel. The acquired knowledge and skills regarding firearms handling enable border guard officers perform the tasks assigned to the SBGSU more efficiently, feel confident while protecting the state border, when performing detention of border violators, and also organize shooting exercises of the personnel of the unit in a safe and secure manner. Such knowledge and skills are acquired by the cadets of the National Academy of the SBGSU while studying the "Firearms Training" discipline. It is presented as a set of activities aimed at studying the legality of using firearms and improving the skills of safe and secure shooting at stationary and moving targets from different positions in a limited time, and in motion. Such training includes studying the safety measures when handling weapons, knowledge of parts of small arms, as well as peculiarities of practical training with weapons and organization of shooting exercises. The purpose of firearms training at the National Academy is to prepare officers of the primary level of the State Border Guard Service of Ukraine to act with weapons in various situations of operational and service activity and to lawfully stop illegal actions as part of a unit, group and independently.